Trichoscopy of Noncicatricial Pressure-induced Alopecia Resembling Alopecia Areata - Papaiordanou, Francine (Int J Trichology, 2016)
Pressure-induced alopecia is an unusual cause of hair loss, and reports of its trichoscopic features are scarce. In this paper, we describe a case of pressure-induced alopecia in which trichoscopic and histopathological findings overlap with those described for alopecia areata.